Morphogenesis and characterization of some epresentative soil profiles from the Old Brahmaputra floodplain in Bangladesh in relation to their agricultural use potential (Bangladesh Journal of Scientific Research, 2011)
Key words: Brahmaputra floodplain; soil characteristics; pedogenesis; soil taxonomyBangladesh J. Sci. Res. 23(1): 27-38, 2010 (June)